Carbon-coated titanium dioxide nano-catalyst, positive plate and preparation method of lithium-sulfur battery

The titanium dioxide nanoparticle catalyst coated with carbon oxide layer solves the problem of slow polysulfide shuttle and conversion kinetics in lithium-sulfur batteries, and efficient adsorption and conversion of polysulfides are achieved, thereby improving the cycle stability and rate performance of the battery.

CN119565582AActive Publication Date: 2025-03-07ANHUI UNIV

Patent Information

Application Number
CN202411767344.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Due to the poor conductivity of sulfur and the slow shuttle and conversion kinetics of polysulfides, lithium-sulfur batteries have fast capacity decay and poor cycle stability, which has hindered commercial feasibility.

Method used

The titanium dioxide nanoparticle catalyst coated with carbon oxide layer increases the porosity and specific surface area of ​​the material through surface oxidation technology, introduces more C-O active sites, enhances the adsorption capacity of polysulfides, and applies this material to the positive electrode of lithium sulfur batteries.

Benefits of technology

The kinetics of the adsorption and conversion reaction of the catalyst to polysulfides are significantly improved, and the cycle stability and rate performance of lithium-sulfur batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565582A_ABST
    Figure CN119565582A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium-sulfur battery preparation, and discloses a surface oxidation technology for improving the adsorption performance of a lithium-sulfur battery, which comprises the following steps: stirring and mixing isopropyl titanate and ethanol, adding polyacrylonitrile, stirring and dissolving, and freeze-drying the solution to obtain a precursor; calcining the precursor in an inert atmosphere for 4-8 hours to obtain carbon-coated titanium dioxide nanoparticles; and then the carbon-coated titanium dioxide nano-particles are placed under ozone to be etched for 30-90 min, and finally the oxidized carbon-coated titanium dioxide nano-particles are obtained. The invention provides a surface oxidation technology for improving the adsorption performance of the lithium-sulfur battery, the porosity and the specific surface area of a carbon-coated nano material are effectively improved, the adsorption capacity on polysulfide is improved, and the cycling stability of the lithium-sulfur battery is improved. The method is simple to operate and easy to synthesize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-sulfur battery preparation, and in particular to an oxidized carbon-coated titanium dioxide nanocatalyst, a positive electrode sheet and a lithium-sulfur battery preparation method. Background Art

[0002] With the rapid development of the new energy industry and the rise of various portable electronic devices, the demand for batteries with high energy density and long cycle life is increasing. Among the technologies that "surpass lithium-ion batteries", lithium-sulfur batteries are popular due to their low cost and high theoretical capacity (1675mAh g -1 ) and high energy density (2600Wh kg -1 ) and other advantages, making it one of the most promising candidate batteries. However, the commercial feasibility of lithium-sulfur batteries is seriously hindered by the poor conductivity of sulfur and the severe shuttling and slow conversion kinetics of soluble polysulfides.

[0003] Among them, the shuttling of polysulfides between the positive and negative electrodes is one of the important reasons for the rapid capacity decay and poor cycle stability of lithium-sulfur batteries. To solve the above problems, the main method currently used is to load or incorporate catalyst materials into lithium-sulfur batteries, such as diaphragm modification and sulfur host material functionalization, to promote the adsorption and conversion of polysulfides and improve the battery cycle life. Carbon-coated materials, as one of the catalyst materials for lithium-sulfur batteries, play a huge role in lithium-sulfur batteries, thanks to the following properties of the material: (1) The surface carbon layer can serve as a stable interface to protect the internal active substances from direct contact with the electrolyte, thereby reducing potential adverse reactions on the particle surface and helping to improve cycle stability and battery life. (2) The carbon layer is wrapped around the active substance to form a continuous conductive network, which promotes the rapid transfer of electrons inside the electrode material and significantly improves the overall conductivity of the composite material, thereby improving the battery's charge and discharge performance. (3) The surface carbon layer can provide a buffer for the active substance, reduce the volume expansion and contraction of the active substance during the charge and discharge process, and help maintain the integrity of the material structure, thereby improving the battery's cycle performance. However, some carbon-coated materials cannot maximize their catalytic performance due to problems such as tight particle distribution, small carbon layer spacing, and shielding of active sites. Summary of the invention

[0004] In order to solve the technical problems raised in the background technology, the present invention provides a titanium dioxide nanoparticle catalyst coated with an oxidized carbon layer, a positive electrode sheet and a lithium-sulfur battery preparation method.

[0005] The present invention provides a catalyst material surface oxidation technology, which increases the porosity of the material, improves the specific surface area of ​​the material, and introduces more CO active sites to enhance the adsorption of polysulfides without destroying the original structure of the carbon-coated material. In addition, the material is used to replace conductive carbon black in the positive electrode of a lithium-sulfur battery, which accelerates the conversion reaction kinetics of polysulfides while ensuring the effective transmission of electrons in the lithium-sulfur battery. The catalyst battery treated by this technology not only has obvious adsorption performance, but also has good cycle stability and rate performance.

[0006] The present invention is implemented by the following technical solution: A method for preparing titanium dioxide nanoparticles coated with an oxidized carbon layer, characterized in that it comprises the following steps:

[0007] isopropyl titanate and ethanol are stirred and mixed, polyacrylonitrile is added, and stirred to dissolve to obtain a precursor solution;

[0008] The precursor material is then processed by freeze drying technology, and the dried material is then calcined for 4-8 hours under an inert atmosphere to obtain carbon-coated titanium dioxide nanoparticles;

[0009] The obtained carbon-coated titanium dioxide nanoparticles are etched under ozone for 30 to 90 minutes, and finally titanium dioxide nanoparticles coated with an oxidized carbon layer are obtained.

[0010] Preferably, the mass fraction of isopropyl titanate in the precursor solution is 1.0-3.0wt%, the mass fraction of polyacrylonitrile is 6.0-10.0wt%, and the amount of ethanol is 10-40mL; the solution is stirred for 4-8h; and the freeze-drying time is 36-48h.

[0011] Preferably, the precursor material is moved to a tube furnace for calcination, and then calcined at 600-800° C. for 4-8 h under an argon atmosphere with an argon gas flow rate of 20-50 mL min-1, and then cooled after annealing.

[0012] Preferably, the ozone purity is 20-40%, and the treatment time is 30-90 minutes.

[0013] The invention provides a titanium dioxide nanoparticle coated with an oxidized carbon layer, which is prepared by the above method.

[0014] The present invention provides a method for preparing a positive electrode sheet, comprising the following steps: melting sulfur and multi-walled carbon nanotubes in a certain ratio to obtain negative sulfur carbon nanotubes, then mixing the negative sulfur carbon nanotubes, conductive carbon black, the catalyst as claimed in claim 5, and a binder in a certain ratio to obtain a slurry, uniformly coating the obtained slurry on a current collector, drying and cutting to obtain a battery positive electrode sheet;

[0015] The catalyst and the binder are mixed in a suitable ratio, the obtained slurry is evenly coated on the current collector, dried and cut to obtain symmetrical battery pole pieces.

[0016] Furthermore, the ratio of sulfur:multi-walled carbon nanotubes is 3:2, and the ratio of negative sulfur carbon nanotubes:conductive carbon black:catalyst:binder is 8:1:1:1.

[0017] Furthermore, the ratio of sulfur:multi-walled carbon nanotubes is 7:3, and the ratio of negative sulfur carbon nanotubes:conductive carbon black:catalyst:binder is 7:2:1:1.

[0018] Preferably, the pole piece is dried at a temperature of 40 to 60° C. for 6 to 8 hours.

[0019] The present invention conducts a visual adsorption experiment, which is as follows:

[0020] In an anhydrous and oxygen-free glove box, sublimed sulfur and lithium sulfide were dissolved in a certain amount of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (volume ratio of 1:1) in a ratio of 5:1 (molar ratio), heated and stirred for 48 hours to obtain a 0.05M Li2S6 solution. The above solution was then diluted to a certain concentration with DOL / DME (volume ratio of 1:1) solvent, and appropriate amounts of catalysts were added to a certain amount of diluent, shaken, and allowed to stand for 10 hours, and the color change of the solution was recorded. Subsequently, a small amount of the supernatant after adsorption was taken, diluted a certain multiple with anhydrous ethanol, and UV-visible spectroscopy was performed.

[0021] The present invention provides a lithium-sulfur battery assembly method, comprising the following steps: in an anhydrous and oxygen-free glove box, assembling in sequence a positive electrode shell, a positive electrode sheet obtained by any method of claim 6-9, an electrolyte, a diaphragm, a lithium sheet, a gasket, and a negative electrode shell, and then pressing with a packaging machine to obtain a button-type lithium-sulfur battery;

[0022] In a water-free and oxygen-free glove box, the positive electrode shell, electrode piece, electrolyte, diaphragm, electrolyte, electrode piece, gasket, and negative electrode shell are assembled in sequence, and then pressed with a packaging machine to obtain a symmetrical battery.

[0023] Compared with the unoxidized catalyst, the catalyst treated by the present invention has a significantly improved adsorption effect on polysulfide, and the symmetrical battery test results also show that this technology can improve the conversion reaction kinetics of the catalyst and polysulfide. In addition, compared with the unoxidized catalyst battery, the cycle stability and rate performance of the battery assembled after the treatment of the present invention are greatly improved.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention provides a method for preparing a titanium dioxide nanomaterial coated with an oxidized carbon layer, wherein a precursor material is obtained by simple chemical synthesis, and then a carbon-coated nanomaterial is obtained by a step of calcination. The method is simple to operate and easy to synthesize.

[0026] 2. The present invention provides a simple surface oxidation technology that can increase the specific surface area of ​​the material, enhance the adsorption and conversion performance of polysulfides, and accelerate the conversion kinetics of polysulfides. The oxygen-treated carbon-coated nanomaterial is prepared into a lithium-sulfur battery positive electrode. In the multi-step conversion process of sulfur species, the intermediate polysulfide is quickly adsorbed and converted, which helps to improve the cycle stability of the lithium-sulfur battery.

[0027] 3. The present invention provides a method for preparing a positive electrode of a lithium-sulfur battery. A catalyst is applied to a sulfur positive electrode to make a positive electrode sheet, which not only ensures the transmission efficiency of electrons, but also effectively inhibits the shuttling of polysulfides. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is an X-ray diffraction (XRD) diagram of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention before and after oxidation treatment.

[0029] Figure 2 The figures are transmission electron microscope (TEM) images of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention before and after oxidation treatment.

[0030] Figure 3 It is a high-resolution transmission electron microscope (HR-TEM) image of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention before and after oxidation treatment.

[0031] Figure 4 It is the adsorption-desorption curve and pore size distribution diagram of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention before and after oxidation treatment.

[0032] Figure 5 It is an infrared spectrum (IR) diagram of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention before and after oxidation treatment.

[0033] Figure 6 It is the ultraviolet-visible absorption spectrum of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention before and after oxidation treatment after adsorption of Li2S6.

[0034] Figure 7 It is a symmetrical battery cyclic voltammetry (CV) curve diagram and a Tafel slope curve diagram of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention before and after oxidation treatment.

[0035] Figure 8It is a charge and discharge curve diagram of a lithium-sulfur battery assembled before and after oxidation treatment of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention at 0.1C.

[0036] Fig. 9 It is a cyclic voltammetry (CV) diagram of a lithium-sulfur battery assembled before and after oxidation treatment of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention at 0.1 mV s-1.

[0037] Fig.10 It is a cycle performance diagram of a lithium-sulfur battery assembled before and after oxidation treatment of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention at a 1C rate.

[0038] Fig.11 It is a rate performance diagram of a lithium-sulfur battery assembled before and after oxidation treatment of the carbon-coated titanium dioxide nanoparticle catalyst prepared by the present invention at 0.2C to 5C. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0040] The chemical reagents used in the present invention are all analytically pure isopropyl titanate, ethanol, and polyacrylonitrile. The sublimated sulfur used was purchased from Sinopharm Chemical Reagent Co., Ltd., and the multi-walled carbon nanotubes were purchased from Shenzhen Suiheng Technology Co., Ltd. The electrolyte and diaphragm used in step 4 were purchased from Suzhou Duoduo Chemical Technology Co., Ltd.

[0041] Embodiment 1:

[0042] Preparation of catalyst: 300 μL of isopropyl titanate was dissolved in 20 mL of anhydrous ethanol and stirred for 5 min. 1.8 g of polyacrylonitrile was added and stirred for 6 h to obtain a precursor solution. The solution was then freeze-dried in a freeze dryer for 36 h. Subsequently, the precursor material was heated at 5 °C min-1 under an argon atmosphere. -1 The temperature was raised to 600° C. in a tube furnace at a heating rate of , and annealed for 4 hours. Afterwards, the obtained material was treated in 30% ozone for 60 minutes to achieve oxidation treatment on the surface of the material, and obtained oxygen-treated carbon-coated titanium dioxide nanoparticles.

[0043] Example 2: Preparation of pole piece: (1) Sublimed sulfur and multi-walled carbon nanotubes are mixed in a ratio of 7:3, and then melted at 155°C for 12 hours to obtain negative sulfur carbon nanotubes. Subsequently, negative sulfur carbon nanotubes: conductive carbon black: catalyst: binder are mixed in a ratio of 7:2:1:1 (wherein the binder is polyvinylidene fluoride), and an appropriate amount of N-methylpyrrolidone solvent is added, and the mixture is ground into a uniform slurry, which is then coated on a current collector (the current collector is carbon-coated aluminum foil), vacuum dried at 60°C for 8 hours, and then cut into discs with a diameter of 12 mm to obtain a positive electrode of the battery. (2) The catalyst and the binder are mixed in a suitable ratio to obtain a uniform slurry, which is then coated on a current collector, vacuum dried at 60°C for 8 hours, and then cut into discs with a diameter of 12 mm to obtain a symmetrical battery pole piece.

[0044] Example 3: Assembly of lithium-sulfur battery: (1) The lithium-sulfur battery was assembled in an argon-filled glove box with a water content of less than 0.01ppm and an oxygen content of less than 0.2ppm. First, the positive electrode sheet containing the catalyst was placed in a CR2016 positive electrode shell, and 20μL of lithium-sulfur battery electrolyte (a mixed solution of 1M lithium bistrifluoromethanesulfonyl imide (LiTFSI) and 1% lithium nitrate (LiNO3) in 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (volume ratio of 1:1)) was added, and then Celgard2500 diaphragm, 14mm commercial lithium sheet, stainless steel gasket, and negative electrode shell were placed in turn to encapsulate a button lithium-sulfur battery. For the battery electrochemical performance test, the battery was first formed at a rate of 0.1C, and then a cycle test was performed at 1C, with a test voltage range of 1.7 to 2.8V. (2) Other conditions remain unchanged, the positive and negative electrodes are replaced with the symmetrical battery electrodes prepared in step 2, 20 μL of 0.05M Li2S6 prepared in step 2 is added to the positive electrode side, and 20 μL of the above lithium-sulfur battery electrolyte is added to the negative electrode side. The positive electrode shell, electrode, electrolyte, diaphragm, electrolyte, electrode, gasket, and negative electrode shell are assembled in sequence, and the symmetrical battery is encapsulated. The voltage range of the symmetrical battery cyclic voltammetry test is -1 to 1 V, and the scan rate is 1 mV s -1 .

[0045] Experimental example: Implementation of visual adsorption experiment: In a water-free and oxygen-free glove box, 80 mg of sublimed sulfur and 23 mg of lithium sulfide were dissolved in 10 mL of a mixed solvent of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (volume ratio of 1:1), heated and stirred for 48 hours to obtain a 0.05M Li2S6 solution. The above solution was then diluted 20 times with DOL / DME (volume ratio of 1:1) solvent, and 15 mg of catalyst was taken in 2 mL of the diluent, shaken, and allowed to stand for 10 hours, and the color change of the solution was recorded. Then a small amount of the supernatant after adsorption was taken, diluted 100 times with anhydrous ethanol, and UV-visible spectroscopy was performed.

[0046] Comparative Example 1:

[0047] Comparative Example 1 provides a method for preparing a catalyst material. Other conditions are the same as those of Example 1, with the only difference being that in step 1 of Example 1, the material is not subjected to ozone treatment after annealing.

[0048] Result analysis:

[0049] As attached Figure 1 As shown, there is no shift in the X-ray diffraction peaks of the catalyst before and after oxygen treatment, indicating that this technology of oxygen treatment of the material will not change the physical phase structure of the catalyst material, which remains in the anatase phase.

[0050] As attached Figure 2 As shown in the TEM image, there are looser pores between the catalyst particles after oxygen treatment.

[0051] As attached Figure 3 As shown, the lattice spacing of the catalyst before and after oxygen treatment is 0.362nm and 0.361nm, respectively, belonging to the (101) crystal plane of the rutile phase, and the lattice fringes of the catalyst after oxygen treatment are more obvious, indicating that this technology will not change the material phase, but can expose more catalyst active sites.

[0052] As attached Figure 4 As shown in Figure 2, the pores of the catalyst after oxygen treatment increased and the BET specific surface area increased significantly, nearly 6 times that of the catalyst before treatment. Figure 2 Analysis shows that this is because part of the carbon layer of the catalyst peels off after surface oxidation treatment, exposing more pores and increasing the specific surface area of ​​the material.

[0053] As attached Figure 5 As shown in the infrared spectrum curves before and after oxygen treatment, it can be seen that the CO stretching vibration peak of the embodiment is strong, and the number of carbon and oxygen binding sites on the catalyst increases. This shows that after the introduction of oxygen, part of the carbon on the catalyst surface is converted, providing more pores, and part of the carbon is combined with oxygen, which enhances the oxidation activity of the catalyst material and is beneficial to the adsorption and conversion of polysulfide by the catalyst.

[0054] As attached Figure 6 The results of the visualized polysulfide adsorption experiment show that after 10 hours, the color of the Li2S6 solution of the embodiment has completely become transparent, while the color of the comparative solution has almost no change compared with the original solution. At the same time, the ultraviolet-visible absorption spectrum test of the supernatant of each solution shows that the absorbance of the embodiment is the lowest. These results show that the adsorption conversion of polysulfides can be effectively improved after the surface oxidation treatment of the material.

[0055] As attached Figure 7As shown, the CV curve results of the symmetrical battery show that the lithium-sulfur battery of the embodiment has a higher response current, and the Tafel fitting curve results show that the redox current density of the embodiment is higher. These results indicate that after the surface oxidation treatment of the material, the redox conversion kinetics of polysulfides is accelerated, which is beneficial to inhibit the shuttling of polysulfides and improve the cycle stability of the lithium-sulfur battery.

[0056] As attached Figure 8 As shown in the figure, it can be seen from the first cycle charge and discharge curve of the battery at 0.1C that compared with the battery discharge capacity of the comparative example (1110.11 mAh g -1 ), the battery in the embodiment shows a higher discharge specific capacity, which can reach 1212.17 mAh g -1 , indicating that the catalytic performance of the material is significantly improved after oxidation treatment.

[0057] As attached Fig. 9 As shown, the lithium-sulfur battery has a current of 0.1 mV s -1 The CV curves below show that the embodiment has a higher response current and a larger integrated area than the comparative example, which indicates that the redox conversion kinetics of the battery of the embodiment is faster and can provide a higher battery capacity.

[0058] As attached Fig.10 As shown in the figure, the cycle curve of the lithium-sulfur battery after 600 cycles at a rate of 1C shows that the embodiment has good cycle capacity and cycle stability. After 600 cycles, the capacity retention rate of the embodiment is 77.24%, with an average decay of 0.037% per cycle, while the average decay of the comparative example is 0.043% per cycle, indicating that the material can promote the conversion of polysulfides and reduce the capacity decay caused by the shuttling of polysulfides.

[0059] As attached Fig.11 As shown in the cycle rate diagram of the lithium-sulfur battery at different rates, it can be seen that the discharge specific capacity of the embodiment at 0.2C, 0.5C, 1C, 2C, and 5C is 829.04 mAh g -1 、655.22mAh g -1 , 594.93mAh g -1 、518.13mAhg -1 , 412.95mAh g -1 , and the capacity remains stable when returning to the low rate after high rate cycling. At the same time, compared with the comparative example, the embodiment also maintains higher capacity stability under high rate conditions.

[0060] Therefore, according to the experimental results, it can be seen that the catalyst material after oxygen treatment can enhance the adsorption conversion performance of lithium-sulfur batteries, accelerate the redox conversion kinetics of lithium-sulfur batteries, and improve the battery's discharge specific capacity, cycle stability and rate performance.

[0061] The present invention provides a surface oxidation technology that can effectively increase the specific surface area of ​​the material, improve the material's adsorption capacity for polysulfides, promote the conversion between sulfur species, and accelerate the reaction kinetics of lithium-sulfur batteries. In addition, the method is simple to operate, low in cost, and is conducive to the large-scale synthesis and preparation of materials. The present invention provides a new solution to solve the problems of poor adsorption performance and low conversion efficiency of carbon-coated catalyst materials for lithium-sulfur batteries:

[0062] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing a carbon-coated titanium dioxide nanocatalyst, characterized in that: The steps include: Isopropyl titanate and ethanol are stirred and mixed, polyacrylonitrile is added, and the mixture is stirred and dissolved. The solution is freeze-dried and then calcined under an inert atmosphere for 4-8 hours to obtain carbon-coated titanium dioxide nanoparticles; The obtained carbon-coated titanium dioxide nanoparticles are then etched under ozone for 30 to 90 minutes to finally obtain titanium dioxide nanoparticles coated with an oxidized carbon layer.

2. The method for preparing a carbon-coated titanium dioxide nanocatalyst according to claim 1, characterized in that: The mass fraction of isopropyl titanate in the precursor solution is 1.0-3.0wt%, the mass fraction of polyacrylonitrile is 6.0-10.0wt%, and the amount of ethanol is 10-40mL; the solution is stirred for 4-8h; and the freeze-drying time is 36-48h.

3. The method for preparing a carbon-coated titanium dioxide nanocatalyst according to claim 1, characterized in that: The precursor was moved to a tube furnace for calcination, and then argon gas was calcined under an argon atmosphere at a flow rate of 20-50 mL min -1 , calcine at 600-800℃ for 4-8h, anneal and then cool down.

4. The method for preparing a titanium dioxide nanocatalyst coated with an oxidized carbon layer according to claim 1, characterized in that: The ozone purity is 20-40%, and the treatment time is 30-90 minutes.

5. A titanium dioxide nanoparticle coated with an oxidized carbon layer, characterized in that: The method is prepared by the method according to any one of claims 1 to 4.

6. A method for preparing a positive electrode sheet, characterized in that: The method comprises the following steps: melting sulfur and multi-walled carbon nanotubes in a certain ratio to obtain negative sulfur carbon nanotubes, then mixing the negative sulfur carbon nanotubes, the catalyst as claimed in claim 5, and a binder in a certain ratio to obtain a slurry, uniformly coating the obtained slurry on a current collector, drying and cutting, and obtaining a positive electrode sheet of a battery; The catalyst and the binder are mixed in a suitable ratio, the obtained slurry is evenly coated on the current collector, dried and cut to obtain symmetrical battery pole pieces.

7. The method for preparing a positive electrode sheet according to claim 6, characterized in that: The ratio of sulfur:multi-walled carbon nanotubes is 3:2, and the ratio of negative sulfur carbon nanotubes:conductive carbon black:catalyst:binder is 8:1:1:

1.

8. The method for preparing a positive electrode sheet according to claim 6, characterized in that: The ratio of sulfur:multi-walled carbon nanotubes is 7:3, and the ratio of negative sulfur carbon nanotubes:conductive carbon black:catalyst:binder is 7:2:1:

1.

9. The method for preparing a positive electrode sheet according to claim 6, characterized in that: The pole piece is dried at a temperature of 40 to 60° C. for 6 to 8 hours.

10. A lithium-sulfur battery assembly method, characterized in that: The method comprises the following steps: in a water-free and oxygen-free glove box, assembling in sequence a positive electrode shell, a positive electrode sheet obtained by any method of claims 6 to 9, an electrolyte, a diaphragm, a lithium sheet, a gasket, and a negative electrode shell, and then pressing with a packaging machine to obtain a button-type lithium-sulfur battery; In a water-free and oxygen-free glove box, the positive electrode shell, electrode piece, electrolyte, diaphragm, electrolyte, electrode piece, gasket, and negative electrode shell are assembled in sequence, and then pressed with a packaging machine to obtain a symmetrical battery.

Citation Information

Patent Citations

  • Preparation method of silicon-carbon negative electrode material for lithium ion battery

    CN104538607A

  • Preparation method of carbon-coated mesoporous lithium titanium phosphate

    CN105375015A

  • Nanometer titanium dioxide composite nitrogen-doped carbon nanofibers and preparation method and application thereof

    CN109037618A

  • Lithium-sulfur battery conductive agent based on nano transition metal phosphide / carbon composite material as well as preparation method and application of lithium-sulfur battery conductive agent

    CN111477873A

  • Method for recycling ternary battery positive electrode material through combination of plasma and ozone

    CN114583124A

Cited By

  • Lithium-sulfur battery catalyst performance test system

    CN223205419U